2020
DOI: 10.30880/ijie.2020.12.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of Dual Wavelength Fiber Laser using different SOAs

Abstract: We investigated the performance of a dual-wavelength fiber laser using different types of semiconductor optical amplifiers (SOAs) utilizing fiber Bragg gratings (FBGs) as comb filter. The lasing performances of linear SOA (LSOA), nonlinear SOA (NLSOA) and booster optical amplifier (BOA) at different current setting were observed. LSOA produced the flattest spectrum based on its peak power difference at only 4.5 dB as compared to 66.4 dB using BOA. BOA has the worst flatness because its polarization sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Besides that, SOA has a simpler setup than EDFA since it does not require optical pumping. Based on SOA's advantage, there is an increasing number of studies on the generation of multiwavelength SOA fiber lasers with different comb filters [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, SOA has a simpler setup than EDFA since it does not require optical pumping. Based on SOA's advantage, there is an increasing number of studies on the generation of multiwavelength SOA fiber lasers with different comb filters [10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sulaiman et al demonstrated using a Sagnac loop mirror [SLM] interferometer, producing 164 lasing lines by adjusting the PCs [17]. Other than the studies mentioned earlier, fiber Bragg grating (FBG) [15] and Mach-Zehnder interferometer (MZI) [18] also received significant interest from other researchers. There are also studies on the combination of two comb filters in a system [8,[19][20].…”
Section: Introductionmentioning
confidence: 99%